The association between insight and depressive symptoms in schizophrenia: Undirected and Bayesian network analyses. Issue 1 (6th May 2020) - Amore, Mario; Murri, Martino Belvederi; Calcagno, Pietro; Rocca, Paola; Rossi, Alessandro; Aguglia, Eugenio; Bellomo, Antonello; Blasi, Giuseppe; Carpiniello, Bernardo; Cuomo, Alessandro; dell'Osso, Liliana; di Giannantonio, Massimo; et al.
Abstract: Background: Greater levels of insight may be linked with depressive symptoms among patients with schizophrenia, however, it would be useful to characterize this association at symptom-level, in order to inform research on interventions. Methods: Data on depressive symptoms (Calgary Depression Scale for Schizophrenia) and insight (G12 item from the Positive and Negative Syndrome Scale) were obtained from 921 community-dwelling, clinically-stable individuals with a DSM-IV diagnosis of schizophrenia, recruited in a nationwide multicenter study. Network analysis was used to explore the most relevant connections between insight and depressive symptoms, including potential confounders in the model (neurocognitive and social-cognitive functioning, positive, negative and disorganization symptoms, extrapyramidal symptoms, hostility, internalized stigma, and perceived discrimination). Bayesian network analysis was used to estimate a directed acyclic graph (DAG) while investigating the most likely direction of the putative causal association between insight and depression. Results: After adjusting for confounders, better levels of insight were associated with greater self-depreciation, pathological guilt, morning depression and suicidal ideation. No difference in global network structure was detected for socioeconomic status, service engagement or illness severity. The DAG confirmed the presence of an association between greater insight and self-depreciation, suggesting the more probable causal direction was from insight to depressive symptoms. Conclusions: In schizophrenia, better levels of insight may cause self-depreciation and, possibly, other depressive symptoms. Person-centered and narrative psychotherapeutic approaches may be particularly fit to improve patient insight without dampening self-esteem. Highlights: Better insight seems associated with depressive symptoms in schizophrenia. Network analyses were used to explore this association in a large sample. Insight was associated with self-depreciation, guilt, and suicidal ideation. Although cross-sectional, data suggest causal direction from insight to depression.